O Magmatismo granítico e os seus efeitos na região de Xambioá/Araguanã, To - POINSIGNON, Janaina Reis (Universidade Federal do Pará, 2019)
The Xambioá region is located in the eastern part of Arguaia belt, in the northern portion of the domain of Estrondo Group (northwest of the State of Tocantins). The granites of Ramal do Lontra and Serra da Ametista, intrusive in the rocks of Estrondo Group, were until recently, the only felsic bodies known in the region. More recent geological observations, during detailed geological mapping, identified several intrusive granitic bodies, generally small, as well as in many sectors, unequivocal signs of albitization, greisenization and caulinization in both granitic bodies and host rocks. Quartz vein systems, host of hyaline quartz and eventually amethyst are commonly associated with granitic intrusions and/or with altered host rocks. The felsic magmatism expressed by the emplacement of alkali-granites (Ramal do Lontra and Serra da Ametista granites and occurrences of Fazenda Novo Horizonte, Fazenda Bela Vista, Fazenda Belém, Morro das Antenas and adjacency) and of albite-granites (Araguaci and sector of Pedra Preta granites). Fine to medium-grained alkali-granites, are usually deformed. These bodies have been considered late-tectonic and correspond most likely to apical zones of larger granitic intrusions, not yet exposed. Fine to medium-grained albite-granites consist essentially of albite, like euhedral crystals, and quartz do not show deformation. It has been interpreted as products of extreme granitic magma differentiation, which originated the alkali-granite. The postmagmatic context had a complex development, resulting in the formation of quartz vein systems and marked alteration of both the intrusive garnitic rocks and host rocks of Estrondo Group formations and the Archean basement. Based on fluid inclusions studies of vein quartz, two types of fluids have been recognized: aqueous- carbonic and aqueous. The first, with high salinity (38 to 53% eq of NaCl) and temperature (340 to 500°C) of metamorphic origin with important magmatic contribution, may have caused the formation of the early milky quartz, and probably the metasomatic alterations at high temperature, namely the albitization and greisenization of both granitic intrusions and host rocks. The second type, of moderate to low temperature and salinity (to 120 from 200°C and 1 to 18% eq of NaCl), is interpreted as having a magmatic origin and after mixing with meteoric waters caused its temperature and salinity decrease. It is possible that the drops in temperature and salinity may have been, in part, resulted from the natural cooling of hydrothermal process. These fluids were responsible for the formation of hyaline quartz, in distensive context of decreasing pressure. They also caused the alteration of igneous rocks and host rocks at low temperature, essentially kaolinization. The albitization was the earliest metasomatic alteration. At high temperature and alkaline conditions, it affected both alkali-granites and albite-granites, and the nearby host formations. Albitite with riebeckite and aegirine resulted also from this process. Strong signs of albitization were also detected in the Estrondo Group rocks and Complexo Colméia, regardless of any magmatic influence, what suggests the possibility of this process not be local but regional and related to the regional metamorphism or dynamometamorphism that acted during the structural evolution of Araguaia belt. The greisenization, even more local, succeeds to albitization, at high temperature but in acidic conditions. It is restricted to immediately host rocks of the intrusive granitic bodies and probably to their marginal portions. At last, at lower temperatures and acidic conditions, kaolinization occurred and their effects have been observed only in the host schists, although this alteration may have also affected the intrusive bodies. The total destruction of all primary minerals but not quartz, resulted in the formation of pure kaolin consisting of kaolinite of high crystallinity.The geochemical data reveal coherence between several processes, like the concentration of trace elements (Th, U, Hf, Nb, Zr, V and W) very common in granitic environment.The results obtained in this study suggest that magmatic/ hydrothermal manifestations have been more intense that believed before, being recommended the continuation of investigations, in more meridian zones of the Estrondo Group domain.